Magnitude, determinants, and complications of short inter pregnancy intervals among pregnant mothers in Ethiopia: a systematic review and meta-analysis - Gizachew Yilak; Biruk Beletew Abate; Alemu Birara Zemariam; Addis Wondmagegn Alamaw; Eyob Shitie Lake; Mulat Ayele; Alemayehu Sayih Belay; Befkad Derese Tilahun (BMC, 2024)
Abstract Introduction Maternal and child mortality remains a major public health concern in Ethiopia. Improving the practice of short inter-pregnancy intervals is a key strategy to reduce neonatal and maternal mortality. Several primary studies conducted in Ethiopia have revealed the practice short inter-pregnancy interval. However, inconsistencies among these studies have been observed, and no review has been conducted to report the combined magnitude, determinants, and complications. Therefore, this review aims to estimate the national magnitude, determinants, and complications of short inter-pregnancy intervals among pregnant mothers in Ethiopia. Methods Following the PRISMA standards, we systematically reviewed and meta-analyzed articles from PubMed, Cochrane Library, and Google Scholar that investigated the magnitude, determinants, and complications of a short inter-pregnancy interval. The Q and I2 tests were used to assess heterogeneity across studies. We utilized a weighted inverse variance random effects model to evaluate the national magnitude and effect size of linked covariates. To examine publication bias, we employed a funnel plot and Egger's regression test. A sensitivity analysis was also performed to determine the impact of the studies. Results The analysis included a total of twenty-six studies. The pooled magnitude of a short inter-pregnancy interval in Ethiopia was found to be 44.054% (95% CI 32.735-55.372; I2 = 100%; P < 0.001). no formal education (AOR = 1.889; 95% CI 1.261-2.517; I2 = 3.42%; P = 0.41), never used contraceptive methods (AOR = 3.38; 95% CI 2.41-4.35; I2 = 44.9%; P = 0.027), breastfeeding duration of less than 24 months (AOR = 6.69; 95% CI 4.77-8.52; I2 = 95.5%; P = 0.00), having a preceding female child (AOR = 1.45; 95% CI 0.88-2.015; I2 = 16.4%; P = 0.301), and experiencing fetal complication (AOR = 3.55; 95% CI 1.986-5.122; I2 = 0%; P = 0.482). Conclusion A substantial number of women in Ethiopia continue to have a short inter-pregnancy interval. To address this issue, it is crucial to focus on empowering women through education and raising awareness about the importance of spacing pregnancies adequately. Efforts should be made to improve breastfeeding practices, promoting the recommended duration of at least 24 months.